Resposta de anticorpos IgE, IgG1 e IgG4 aos componentes ligantes de Concanavalina A isolados de Blomia tropicalis (Acari: Echimyopodidae) em indivíduos alérgicos e não alérgicos - Almeida, Karine Cristine de (2005)
Blomia tropicalis (Bt) and Dermatophagoides pteronyssinus (Dp) are the most prevalent house dust mites in tropical countries and associated with allergic diseases. Glycosilated antigens are highly immunogenic and involved in different pathologies, including allergies. The aims of this study were to evaluate IgE, IgG1, and IgG4 responses to Concanavalin A-binding components (Bt-ConA) isolated from Bt extract in sera of allergic and non-allergic subjects and to analyze the crossreactivity with Dp extract. Also, IgE-, IgG1- and IgG4-reactive antigenic components from both extracts were analyzed by Immunoblotting. Bt-ConA was obtained from Btwhole extract fractionated on Con-A-Sepharose affinity chromatography and both extracts were evaluated in SDS-PAGE and ELISA for IgE, IgG1, and IgG4 in sera of 121 patients with allergic rhinitis and 36 non-allergic subjects. Subjects were skin prick tested (SPT) to Bt-whole extract. Inhibition and immunoblotting test were performed to analyze IgE, IgG1, and IgG4 responses to both extracts. SPT showed that 58% of patients were sensitized to Bt (Bt+), with 52% reactive to both mites (Bt and Dp) and 6% to Bt only. A broad spectrum of proteins (14-152kDa) were visualized in Bt-whole extract and components >27kDa in Bt-ConA extract. ELISA showed a similar profile of IgE, IgG1 and IgG4 levels to Bt-whole and Bt-ConA extracts in different groups, although Bt+ patients showed a lower IgG4 reactivity to Bt-ConA extract. Specific IgG1 levels were higher in Bt+ patients than control subjects, and IgG4 levels showed no significant difference among the groups. ELISA inhibition showed a partial IgE and total IgG1 and IgG4 cross-reactivity with Dp extract for Bt-whole and Bt-ConA extracts. Immunoblotting revealed ten antigenic components in Bt-whole extract (14-152kDa) recognized by IgE and IgG4 antibodies and five of these components (>50kDa) were recognized by IgG1 in Bt+ patients. Bt- ConA extract showed eight antigenic components (27-152kDa), from which the 152 and 123kDa bands were predominantly recognized by IgE, and only three of these components (93, 123 and 152kDa) were recognized by IgG1 while IgG4 antibodies weakly recognized the 66 and 152kDa components in Bt+ patients. It can be concluded that Con A-binding components isolated from Bt constitute major allergens and are involved in both allergen sensitization (IgE response) and homeostase maintenance (IgG1 and IgG4 responses) and that glycosilated components, particularly those of high molecular weight, are preferentially recognized by IgE and IgG1, but not by IgG4 antibodies.